Discontinuation of the Tyrosine Kinase Inhibitor Sunitinib in Patients with Metastatic Renal Cell Carcinoma: A Case Series - Neuhaus, Thomas; Luyken, Joachim; Stier, Sebastian (Urology Journal, 2014)
Abstract Purpose: Tyrosine kinase inhibitors (TKI) play a pivotal role in the modern treatment of patients with metastatic renal cell carcinoma (mRCC). Depending on the course and the response, the targeted therapy may last for years. Thus the question arises, if a successful treatment leading to a complete response or at least a stable disease after a partial remission, may be discontinued. Materials and Methods: Here we present 3 patients with mRCC treated with sunitinib for at least one year, resulting in a partial response, followed by a stable disease for several years. In these patients, the treatment was interrupted for different medical reasons. Results: After a period of 20, 33 and 34 months, respectively, the metastases of the renal cell cancer showed no signs of progression, neither clinically nor in computed tomography scans, but the side effects of TKI or the medical problem leading to treatment interruption resolved in all patients within a few weeks. Conclusion: The discontinuation of the treatment for mRCC with TKI seems to be possible, even in those patients with a partial response only, but no complete remission has been achieved before.